Genetic Diversity and Disease Susceptibility 2018
DOI: 10.5772/intechopen.78029
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptors Gene Polymorphism and Susceptibility to Cancer Development

Abstract: Toll-like receptors (TLRs) play an important role in immune-surveillance and responses towards pathogenic and non-pathogenic microorganisms. They act as innate immune sensors against endogenous and exogenous danger signals by recognizing the pattern recognition molecules (DAMPs and PAMPs) and drive an adaptive immune response through their signaling pathways, which leads to NF-κB and IRF3 transactivation and induces different inflammatory cytokine genes. TLRs polymorphisms were investigated in various cancer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 73 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…3 A study in the south of Iran on 150 patients with colorectal cancer and 150 control people showed a significant relationship between the TLR2 Arg753Gln polymorphism and colorectal cancer [32]. A metaanalysis study revealed that rs5743708 polymorphism was related to hepatocellular carcinoma (HCC) and decreased survival of patients with stages III and IV of advanced colon cancer [33]. Therefore, regardless of whether the rs5743708 polymorphism has a positive or negative effect on cancer, most studies have pointed out the influential role of this polymorphism in cancer.…”
Section: Vol 9 Nomentioning
confidence: 99%
“…3 A study in the south of Iran on 150 patients with colorectal cancer and 150 control people showed a significant relationship between the TLR2 Arg753Gln polymorphism and colorectal cancer [32]. A metaanalysis study revealed that rs5743708 polymorphism was related to hepatocellular carcinoma (HCC) and decreased survival of patients with stages III and IV of advanced colon cancer [33]. Therefore, regardless of whether the rs5743708 polymorphism has a positive or negative effect on cancer, most studies have pointed out the influential role of this polymorphism in cancer.…”
Section: Vol 9 Nomentioning
confidence: 99%